2022
DOI: 10.3389/fgene.2022.869950
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of m6A RNA Methylation in the Aging Process and Aging-Associated Diseases

Abstract: N6-methyladenosine (m6A) is the most common and conserved internal eukaryotic mRNA modification. m6A modification is a dynamic and reversible post-transcriptional regulatory modification, initiated by methylase and removed by RNA demethylase. m6A-binding proteins recognise the m6A modification to regulate gene expression. Recent studies have shown that altered m6A levels and abnormal regulator expression are crucial in the ageing process and the occurrence of age-related diseases. In this review, we summarise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 221 publications
0
16
0
Order By: Relevance
“…m 6 A is regulated by writer, reader, and eraser proteins. 152 , 153 The multi-subunit writer RNA methyltransferases (MTases) are assembled mainly by methyltransferase like 3 (METTL3), METTL14, and Wilms tumor 1 associating protein (WTAP). 154 The first reported m 6 A modification involved in senescence is methylation at the 3ʹ-UTR of the CDKN1A mRNAs by a METTL3/14 heterodimer, which facilitates p21 translation.…”
Section: Epigenetic Regulation Of Agingmentioning
confidence: 99%
“…m 6 A is regulated by writer, reader, and eraser proteins. 152 , 153 The multi-subunit writer RNA methyltransferases (MTases) are assembled mainly by methyltransferase like 3 (METTL3), METTL14, and Wilms tumor 1 associating protein (WTAP). 154 The first reported m 6 A modification involved in senescence is methylation at the 3ʹ-UTR of the CDKN1A mRNAs by a METTL3/14 heterodimer, which facilitates p21 translation.…”
Section: Epigenetic Regulation Of Agingmentioning
confidence: 99%
“…When the DNA damage response (DDR) is prolonged, it promotes senescence [4]. Further known mechanisms underlying senescence are: (1) persistent DDR activation at telomeres, the ends of chromosomes, which is sufficient to activate replicative cell senescence [8]; (2) oncogene activation partly via reactive oxygen species (ROS) production, determining hyperproliferation and altered DNA replication profiles [4,8]; (3) cell cycle arrest by upregulation of p21 and p16 [9]; (4) mitochondrial abnormalities with an increase in ROS synthesis and impairment in biogenesis and mitophagy [10]; (5) induction to resistance to apoptosis by upregulation of the antiapoptotic proteins [10]; (6) metabolic changes determined by senescence-associated-β-galactosidase (SA-β gal) accumulation along with the increase in cellular lysosomal content [10]; (7) large-scale chromatin reorganization occurring with the generation of senescence-associated heterochromatin foci, which suppress transcription of pro-proliferation genes [10]; (8) secretion of pro-inflammatory cytokines, chemokines, proteases, and growth factors that influence the neighbouring cells (SASP profile); (9) morphological alterations including cellular flattening and enlargement [10]; (10) post-transcriptional regulatory pathways taking place at different levels: through the action of mRNA-binding proteins (RBPs) and noncoding RNAs [11][12][13][14]; through a dysregulated splicing factor expression [12,15]; and through N6-methyladenosine (m6A) processes with specific m6A-binding proteins [14].…”
Section: Introductionmentioning
confidence: 99%
“…The research has shown the possibility of the existence of complex senescence regulatory mechanisms including RNA modifications (Sobieszczuk-Nowicka et al, 2018); therefore, investigation of the epigenetic mechanisms participating in leaf senescence is an important research topic. As has already been mentioned the role of m 6 A modifications in the aging of animal models as well as cell senescence has been previously reported (Castro-Hernańdez et al, 2022;Sun et al, 2022b). Recent findings about m 6 A modification in the process of aging include the participation of this modification in cell senescence, inflammation, autophagy, DNA damage, oxidative stress, neurodegenerative diseases, tumors, diabetes, and cardiovascular diseases.…”
mentioning
confidence: 73%